Climate overrides the effects of land use on the functional composition and diversity of Mediterranean reptile assemblages. Issue 1 (18th October 2020) - Barnagaud, Jean‐Yves; Geniez, Philippe; Cheylan, Marc; Crochet, Pierre‐André
Abstract: Aim: To test the hypothesis that spatial variations in climate and land use explain the distribution and diversity of reptiles' ecological traits in a biodiversity hotspot of the Mediterranean basin. Location: French Mediterranean region. Taxon: Reptiles (25 species). Methods: We defined 288 species assemblages from 27, 858 opportunistic occurrence records within 10 × 10 km square grid cells. Using a RLQ analysis, we investigated the distribution of nine ecological traits describing reptiles' reproductive, dietary and behavioural strategies along environmental gradients formed by 10 climatic, topographic and land‐use descriptors. After homogenizing survey effort through rarefaction, we used generalized additive models to assess variations in species richness and several measures of functional diversity and composition along these gradients. Results: Although ecological traits were not structured by environmental gradients at a species level, species richness and all measures of functional diversity varied nonlinearly with climate, elevation and secondarily land use. Species richness and body size peaked at intermediate altitudes, indicating a climatic transition zone between Mediterranean and medio‐European herpetofaunas. Conversely, functional diversity increased from Mediterranean plains, dominated by urbanization and agriculture, to higher elevations. These changes were associated with shifts towards less productive, more diurnal and more forest‐related species. Main conclusions: Species‐scale patterns are insufficient to assess regional variations in ecological traits in space. Our results support the hypothesis that climatic limitations in species' distributions, rather than environmental filtering, explain the taxonomic and ecological diversity of reptiles at a regional scale. Although secondary to climate, land abandonment has a strong structuring effect which may contribute to homogenize the composition of reptile assemblages.